Treatment of ophthalmopathy in the course of Graves’ disease - Woźniak, Magdalena; Tywanek, Ewa; Rudzki, Grzegorz; Świrska, Joanna; Zwolak, Agnieszka; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2019)
ABSTRACT:Introduction: Graves’ disease is an autoimmune disease in which the TSH receptor (TSHR) is an autoantigen. Its stimulation by antibodies inhibiting thyrotropin binding causes increased secretion of free thyroid hormones and consequently symptoms of thyrotoxicosis. Due to the presence of the same antigen also on orbital and skin fibroblasts, after activating the cell response mechanisms, non-thyroid symptoms of the disease appear, i.e. ophthalmopathy. In most patients, ophthalmopathy is mild and resolves spontaneously. However, in about 10% of patients the disease develops severe to moderate form and requires intensive therapy. Purpose: The aim of this paper is to present the treatment options for ophthalmopathy, which is the most common manifestation of non-thyroid symptoms of Graves’ disease, as well as to draw attention to the fact that treatment may be difficult and requires an interdisciplinary approach, and the treatment plan should be individually adapted to each patient. 1,2,3State of knowledge: The first-line treatment according to the guidelines published in 2016 by the European Group on Graves Orbitopathy (EUGOGO) are high doses of glucocorticosteroids administered intravenously. The second-line treatment is repeated use of intravenous steroid cycle, oral therapy with glucocorticoids, then combined with orbital or cyclosporine radiation therapy, rituximab or expectant management approach. Rehabilitation treatment is necessary in most patients after the disease has been inactive and maintained for at least 6 months with vision impairment and/or reduced quality of life.1,2,3,7,9Summary: Ophthalmopathy is the most common non-thyroid manifestation of Graves’ disease. This is a relatively rare disorder, but it has a significant negative impact on the quality of life of people affected by this disease. Therefore, it is very important, both among physicians and patients, to increase the awareness of this disease, apply effective preventive measures and inhibit its progress. Early diagnosis and appropriate treatment are of crucial importance.